Lean seis sigma healthcare: estudo de caso em um hospital privado de Guaratinguetá - Lanaro, Felipe Real Bispo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This final coursework is the consolidation of the research activities performed on the deployment of Lean Six Sigma practices on a healthcare facility, that took place on a private hospital in Guaratinguetá, Brazil. An operational diagnosis was performed on the hospital main activity areas, and after a thorough analysis two main improvement axis with the biggest return potential were selected: supplies management and surgical center optimization. Improvement proposals in these areas were then conceived and evaluated. Among them, those with the greatest benefits were proposed to the hospital direction. This work presents an operational improvement solution portfolio for application on a hospital setting and also makes a detailed analysis of select applied solutions, their results and complexities.

Este trabalho de conclusão de curso é a consolidação das atividades de pesquisa realizadas em um hospital particular da região de Guaratinguetá para a implantação de práticas Lean Seis Sigma na área de saúde. Foi realizado um diagnóstico operacional das principais áreas do hospital, e após análise deste foram estabelecidos dois eixos principais de ações de melhoria com maior potencial de ganho: otimização da gestão de estoques e do centro cirúrgico. Em sequência, proposições de melhoria nessas áreas foram concebidas e avaliadas. Dentre essas, aquelas com maior potencial foram apresentadas para a direção do hospital. Esta pesquisa apresenta um portfolio de soluções potenciais de melhoria operacional para aplicação num ambiente hospitalar e também faz uma análise detalhada de soluções selecionadas aplicadas e seus resultados e complexidades.
Lean six sigma healthcare : a case sudy at a proven hospital in Guaratinguetá
Keywords: Seis sigma (Padrão de controle de qualidade); Saude - Administração; Centros cirúrgicos; Gestão da qualidade total; Six sigma (Quality control standard)